Stress Training in the Classroom: Evidence of Learning Transfer and Psychological Gains - Flinchbaugh, Carol; Moore, Whitney; Gandhi, Shammi (Journal of management education, 2024)
Stress is ubiquitous in life and creates a need for effective responses in any domain. In this exploratory study, our goal was to understand better how business students learn and use stress management techniques in the classroom context and how this learning applies to different domains. We used thematic coding and textual analysis of weekly student journal reflections about their use of different stress management techniques over 12 weeks. Moving beyond their use of stress techniques in the classroom, students’ comments suggest that their broad use of tools, led to improved well-being (i.e., increased positive affect, reduced stress, and negative affect) beyond the classroom into other life domains. An analysis of student statements further showed increases in their present-focused cognitive orientation, the key dimension of mindfulness, over time. Their heightened present-focused cognitive orientation seems to stem from their practice of the deep breathing stress management technique. Thus, the results suggest that an explicit focus on students’ stress reduction in the classroom may have important implications for how educators can better prepare students for addressing stress and improving psychological and cognitive gains through applied learning across multiple life experiences.